THE JOURNALS EDUCATION (1931-1961) AND DIDACTICS: CONTRIBUTIONS OF NORBERT ELIAS - Castro, Rosane Michelli de [UNESP]; Oliveira Reis, Karina Cassia [UNESP] (Univ Metodista Piracicaba-unimep, 2018)
This article results from reflections developed together with the Historical Research Program that aims to gather theoretical contributions to a history of the Didactics course in Brazil (1827-2011). The reflections were carried out focusing on the analysis of aspects of a periodic in its three phases, Education (1931-1932), Education Journals (1933-1944) and Education (1945-1961), documentary corpus for a research, developed at Masters level. A member of the Research Program mentioned. It was an analysis of aspects such as the life cycle of these journals and also aspects related to their materiality and those that materialize in a qualitative-quantitative analysis, referring, for example, to the predominance and recurrence of the themes on Didactics, such as employee information and the number of articles per employee. The theoretical-methodological framework, besides the theorizations of researchers of the History of the school disciplines, was constituted by the formulations of Elias (1999), from the notion of social configuration. We consider it pertinent to establish such a dialogue, considering that the journals analyzed also constituted spaces for materializing these discourses, centrally, on Didactics, in favor of a utilitarian tradition, confirmed at the end, but at the same time, of the academic and pedagogical traditions.
Keywords: HISTORY OF EDUCATION; DIDACTICS; JOURNALS EDUCATION; NORBERT ELIAS; SOCIAL CONFIGURATION